2022
DOI: 10.1525/abt.2022.84.4.202
|View full text |Cite
|
Sign up to set email alerts
|

Developing Young Watershed Citizen Scientists through Professional Partnerships in the Classroom

Abstract: What’s in Our Waters Jr. (WOW Jr.) is an environmental outreach program designed to teach fourth grade elementary students about watershed protection. This program is unique because of the partnership that brings together students, teachers, scientists, and water resource professionals to promote science education and environmental stewardship in the classroom through mentorship and hands-on learning activities. WOW Jr. is co-led by the Clemson University Cooperative Extension Service (4-H Youth Development an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Citizen science projects provide both problem-oriented and project-oriented learning experiences that can be integrated into formal and non-formal education settings. Several studies have indicated that citizen science programs can be effective learning activities when incorporated into the classroom (Aristeidou et al, 2022;Godfrey et al, 2022;Lüsse et al, 2022). By incorporating citizen science into general education, educators can provide authentic research experiences while reducing resource consumption (Vitone et al, 2016).…”
Section: Constructivism Learning Theorymentioning
confidence: 99%
“…Citizen science projects provide both problem-oriented and project-oriented learning experiences that can be integrated into formal and non-formal education settings. Several studies have indicated that citizen science programs can be effective learning activities when incorporated into the classroom (Aristeidou et al, 2022;Godfrey et al, 2022;Lüsse et al, 2022). By incorporating citizen science into general education, educators can provide authentic research experiences while reducing resource consumption (Vitone et al, 2016).…”
Section: Constructivism Learning Theorymentioning
confidence: 99%